Impact of waste segregation training on medical and recyclable waste in an operating theater a quasi experimental study - Büşra Nur Evliya Felek; Süheyla Karadağ Erkoç; Menekşe Özçelik; Dilek Yörükoğlu (Scientific Reports)
Abstract This quasi-experimental study evaluated the effects of waste segregation training on medical and recyclable waste generation in the operating theater of Ankara University Cebeci Hospital. Conducted between March and June 2024, the study included pre-training, post-training, and two-month follow-up waste measurements, alongside a survey assessing staff awareness. A total of 53 operating room staff participated. Training significantly increased the amount of recyclable waste per surgery (from 1.30 kg to 1.80 kg, p = 0.01) in the first month post-training. Although medical waste per surgery decreased (from 4.92 kg to 4.14 kg), the reduction was not statistically significant (p = 0.09). However, two months later, waste levels began reverting to baseline (recyclable: 1.79 kg; medical: 5.07 kg per surgery), suggesting the effect of a single training session may diminish over time. Notably, 40% of doctors lacked sufficient knowledge pre-training, and those favoring training were often the least informed (p = 0.02), highlighting gaps in prior education. This study emphasizes the need for repeated and tailored training programs to reinforce sustainable waste practices in surgical environments.